Abnormal sensory thresholds of dystonic patients are not affected by deep brain stimulation. (19th March 2021) - Listik, Clarice; Cury, Rubens Gisbert; da Silva, Valquiria Aparecida; Casagrande, Sara Carvalho Barbosa; Listik, Eduardo; Link, Naira; Galhardoni, Ricardo; Barbosa, Egberto Reis; Teixeira, Manoel Jacobsen; Ciampi de Andrade, Daniel
Abstract: Background: Unlike motor symptoms, the effects of deep brain stimulation (DBS) on non‐motor symptoms associated with dystonia remain unknown. Methods: The objective of this study was to assess the effects of DBS on evoked experimental pain and cutaneous sensory thresholds in a crossover, double‐blind on/off study and compare these results with those of healthy volunteers (HV). Results: Sixteen patients with idiopathic dystonia (39.9 ± 13 years old, n = 14 generalized) with DBS of the globus pallidus internus underwent a battery of quantitative sensory testing and assessment using a pain top‐down modulation system (conditioned pain modulation, CPM). Results for the more and less dystonic body regions were compared in on and off stimulation. The patients' results were compared to age‐ and sex‐matched HV. Descending pain modulation CPM responses in dystonic patients (on‐DBS, 11.8 ± 40.7; off‐DBS, 1.8 ± 22.1) was abnormally low (defective) compared to HV (−15.6 ± 23.5, respectively p = .006 and p = .042). Cold pain threshold and cold hyperalgesia were 54.8% and 95.7% higher in dystonic patients compared to HV. On‐DBS CPM correlated with higher Burke‐Fahn‐Marsden disability score ( r = 0.598; p = .014). While sensory and pain thresholds were not affected by DBS on/off condition, pain modulation was abnormal in dystonic patients and tended to be aggravated by DBS. Conclusion: The analgesic effects after DBS do not seem to depend on short‐duration changes in cutaneous sensory thresholds in dystonic patients and may be related to changes in the central processing of nociceptive inputs.